Estrutura de comunidades e mecanismos de regeneração natural de um trecho de floresta ribeirinha no bioma Pampa, Brasil - Araujo, Ana Claudia Bentancor (2017)
The change in the characteristics of the environment causes variations in the vegetation creating mosaics with different compositions and structure. The objective of this research was to evaluate the influence of environmental factors in community structure and characterize the mechanisms of natural regeneration in a riverine seasonal forest on Pampa biome, Sant’Ana do Livramento, RS, Brazil. Three levels of inclusion were used for sampling forest communities: arboreal componente (diameter at breast height (DBH) ≥ 5 cm), sampled in 100 plots of 10 m × 10 m (1 ha), natural regeneration Class I (0,1 m ≤ h < 1 m) sampled in 100 sub-plots of 2 m × 2 m (0,04 ha) e natural regeneration Class II (h ≥ 1 m and DBH < 5 cm) sampled in sub-plots of 5 m × 5 m (0,25 ha). In arboreal component were found three floristic groups, by means of cluster analysis (TWISPAN): Group 1, areas near the forest edge; Group 2, low areas near the flow of water channels; Group 3, areas where soils are deeper. For recovery of degraded areas with similar environmental characteristics studied area, was recommended use of Ocotea acutifolia, Pouteria salicifolia, Gymnanthes klotzschiana, Eugenia uniflora, Allophylus edulis, Blepharocalyx salicifolius, Prunus myrtifolia, Scutia buxifolia, Nectandra megapotamica and Styrax leprosus. The species with more developed structure in arboreal component was Ocotea acutifolia and Pouteria salicifolia, and Eugenia uniflora e Blepharocalyx salicifolius in natural regeneration. The species of arboreal component showed association of physical and chemical characteristics of the soil, altimetric quota, and canopy opening. The natural regeneration had association of of physical and chemical characteristics of the soil, altimetric quota, and litter thickness (height) accumulated. The analyzis of environmetal correlations of the most important in the arboreal component indicated that Ocotea acutifolia e Pouteria salicifolia showed greater abundance in land with soils rich in organic matter and exposed to solar luminosity. In the analysis of ecological groups we found that the natural regeneration has kept the same proportions of arboreal component, with a higher proportion of zoochorous dispersal syndrome and light demanding for germination and development of plants, except for stratification of canopy. In characterization of the mechanisms of natural regeneration showed the presence of species with abundant fruit and seed dispersal by animals, and the soil seed bank demonstrated potencial for colonization and restoration of vegetation after disturbances, especially with species herbaceous. The natural regeneration consistent in main mechanism of the regeneration of many tree species of that make up the current structure of the forest. It is concluded that with due consideration to the environmental conditions of the area to be recovered, phytosociology studies and the correlation of species with environmental variables can be an important tool in decision making, as to the strategy to be adopted for the restoration, indicating species were used.